(untitled) (Bangladesh Journal of Pharmacology, 2019)
In order to search more antimicrobial natural products for new drug discovery, bioassay and chemical investigation of endophytic strains from Rumex madaio were carried out. Six fungal strains (numbered as L1, L6, L9, L10, R1, R2) were successfully isolated and their antimicrobial effects on three human pathogens, Escherichia coli, Staphyloccocus aureus and Candida albicans, were evaluated. The results indicated that ethyl acetate extracts of fermentation broth of these strains had no potent antimicorbial activity against E. coli and C. albicans while strains L1 and R1 had stronger inhibitory effects on S. aureus. On basis of morphological characteristics and 18S rRNA sequence analysis, strains L1 and R1 were respectively classified as Colletotrichum and Fusarium geni. The chemical study of strain R1 led to isolation of two known antimicrobial agents, dibutyl phthalate (1) and beauvericin (2). Video Clip of Methodology: 1 min 14 sec: Click to watch